Strain-dependent effects of diazepam and the 5-HT2B/2C receptor antagonist SB 206553 in spontaneously hypertensive and Lewis rats tested in the elevated plus-maze - Takahashi,R.N. (2001)
The 5-HT2B/2C receptor antagonist SB 206553 exerts anxiolytic effects in rat models of anxiety. However, these effects have been reported for standard rat strains, thus raising the issue of SB 206553 effects in rat strains displaying different levels of anxiety. Herein, the effects of SB 206553 in a 5-min elevated plus-maze test of anxiety were compared to those of the reference anxiolytic, diazepam, in two rat strains respectively displaying high (Lewis rats) and low (spontaneously hypertensive rats, SHR) anxiety. Diazepam (0.37, 0.75, or 1.5 mg/kg; 30 min before testing) increased in a dose-dependent manner the behavioral measures in SHR, but not in Lewis rats. On the other hand, SB 206553 (1.25, 2.5, or 5 mg/kg; 30 min before testing) failed to alter the anxiety parameters in both strains, whereas it increased closed arm entries in Lewis rats, suggesting that it elicited hyperactivity in the latter strain. Accordingly, the hypolocomotor effect of the nonselective 5-HT2B/2C receptor agonist m-chlorophenylpiperazine (1.5 mg/kg ip 20 min before a 15-min exposure to an activity cage) was prevented by the 1.25 and 2.5 mg/kg doses of SB 206553 in Lewis rats and SHR, respectively. Compared with SHR, Lewis rats may display a lower response to benzodiazepine-mediated effects and a more efficient control of locomotor activity by 5-HT2B/2C receptors.